Efficacy of pulsed ultraviolet (PUV) light for disinfection of nosocomial pathogens: An in-vitro investigation of key parameters for surface and equipment applications - Mohammad Kazem Sharifi-Yazdi; Sina Sharifi-Yazdi; Sara Sharifi Yazdi (PLoS ONE, 2025)
Hospital-acquired infections remain a persistent challenge, particularly when caused by bacterial strains that have developed resistance to multiple antibiotics. Reports from both clinical wards and public health agencies show how rapidly these organisms adapt, leaving many standard cleaning procedures and treatments far less effective than they once were. This concern prompted us to investigate pulsed ultraviolet (PUV) light from a xenon source as an alternative approach to inactivation, offering rapid action without the use of harsh chemicals. The work involved testing four bacterial species of clinical relevance: Pseudomonas aeruginosa , Staphylococcus aureus , Bacillus cereus , and spores of Bacillus megaterium . We evaluated the impact of UV dose, examined how suspension depth influenced performance, and assessed whether exposure to visible light after treatment could reverse the effect. For all strains, significant microbial reduction was achieved using a broad-spectrum emission with a strong germicidal peak in the 260 nm region. Spores showed much greater resilience than vegetative cells, while increased liquid depth reduced the disinfection efficiency.Some degree of photorepair occurred in non-spore-forming species under standard room lighting. Taken together, these findings indicate that, when tuned to the right parameters, PUV could serve as a valuable addition to hospital disinfection routines, especially for equipment and surfaces that cannot withstand heat or aggressive chemical agents.